Le sentiment linguistique chez Saussure - Siouffi, Gilles (Langages, 2021)
"Everything in the feeling of speakers is a real phenomenon," wrote Saussure in the 1880s for the purpose of a prospective morphology course. But the term feeling is not one of those which, like sign, system, synchrony and diachrony, is associated with the canon of Saussure's concepts. The purpose of this work is to illustrate, on the contrary, that linguistic feeling is essential to the Geneva linguist's reasoning, and that it is perhaps the central focus which enables him to define what he calls "language". The contributions in this work investigate what can be called Saussure's linguistic feeling, by exploring the inspirations which Saussure may have picked up from his predecessors, by studying the various inflections which the motif embraces in his texts, particularly from manuscript sources, and by exploring the issues of the notion today. As it is rooted in the sphere of the history of linguistic ideas, it also has the potential to open up new avenues for research on the apprehension of linguistic facts by the speaker.